All-Trans Retinoic Acid Synergizes with Enasidenib to Induce Differentiation of IDH2-Mutant Acute Myeloid Leukemia Cells - Kim, Yundeok; Jeung, Hoi-Kyung; Cheong, June-Won; Song, Jaewoo; Bae, Soo Han; Lee, Jong In; Min, Yoo Hong (Yonsei medical journal, 2020)
Pharmacological inhibition of mutant isocitrate dehydrogenase (IDH) reduces R-2-hydroxyglutarate (2-HG) levels and restores cellular differentiation in vivo and in vitro. The IDH2 inhibitor enasidenib (AG-221) has been approved by the FDA as a first-in-class inhibitor for the treatment of relapsed or refractory (R/R) IDH2-mutant acute myeloid leukemia (AML). In this study, the effects of a combination of all-trans retinoic acid (ATRA) and AG-221 on AML cell differentiation was explored, along with the mechanisms employed by IDH2-mutant cells in AML.PURPOSEPharmacological inhibition of mutant isocitrate dehydrogenase (IDH) reduces R-2-hydroxyglutarate (2-HG) levels and restores cellular differentiation in vivo and in vitro. The IDH2 inhibitor enasidenib (AG-221) has been approved by the FDA as a first-in-class inhibitor for the treatment of relapsed or refractory (R/R) IDH2-mutant acute myeloid leukemia (AML). In this study, the effects of a combination of all-trans retinoic acid (ATRA) and AG-221 on AML cell differentiation was explored, along with the mechanisms employed by IDH2-mutant cells in AML.We treated the human AML cell line, IDH2-mutant-TF-1, and primary human AML cells carrying IDH2 mutation with 30 μM AG-221 and 100 nM ATRA, alone or in combination.MATERIALS AND METHODSWe treated the human AML cell line, IDH2-mutant-TF-1, and primary human AML cells carrying IDH2 mutation with 30 μM AG-221 and 100 nM ATRA, alone or in combination.Combined treatment with AG-221 and ATRA inhibited 2-HG production and resulted in synergistic effects on differentiation among IDH2-mutant AML cells and primary AML cells expressing IDH2 mutation. Combined treatment with AG-221 and ATRA altered autophagic activity. AG-221 and ATRA treatment-induced differentiation of IDH2-mutant AML cells was associated with autophagy induction, without suppressing autophagy flux at maturation and degradation stages. A RAF-1/MEK/ERK pathway was founded to be associated with AG-221 and ATRA-induced differentiation in IDH2-mutant AML cells. IDH-associated changes in histone methylation markers decreased after AG-221 and ATRA combination treatment.RESULTSCombined treatment with AG-221 and ATRA inhibited 2-HG production and resulted in synergistic effects on differentiation among IDH2-mutant AML cells and primary AML cells expressing IDH2 mutation. Combined treatment with AG-221 and ATRA altered autophagic activity. AG-221 and ATRA treatment-induced differentiation of IDH2-mutant AML cells was associated with autophagy induction, without suppressing autophagy flux at maturation and degradation stages. A RAF-1/MEK/ERK pathway was founded to be associated with AG-221 and ATRA-induced differentiation in IDH2-mutant AML cells. IDH-associated changes in histone methylation markers decreased after AG-221 and ATRA combination treatment.Our preliminary evidence indicates that the addition of ATRA to treatments with IDH2 inhibitor may lead to further improvements or increases in response rates in IDH2-mutant AML patients who do not appear to benefit from treatments with IDH2 inhibitor alone.CONCLUSIONOur preliminary evidence indicates that the addition of ATRA to treatments with IDH2 inhibitor may lead to further improvements or increases in response rates in IDH2-mutant AML patients who do not appear to benefit from treatments with IDH2 inhibitor alone.